Unauthorized Use of Famous Brands In Virtual Products of The Metaverse World In The Perspective of Brand Law And Technology Law In Indonesia - Kimiko Auguchiro Putri Samudra; Tasya Safiranita; Rika Ratna Permata (CV. Publikasi Indonesia, 2023)
The Metaverse is a new form of virtual interactive and physically cyber interaction where users can experience activities in a virtual environment that feels very real. For companies that utilize the Metaverse well, such as promoting or commercializing virtual products within it, it can bring significant profits. However, commercialization through cross-border technology often faces legal issues that arise. The use of brand elements on a product marketed by others without permission is a major issue in the field of brands, which also occurs in the digital world. This study aims to prove legal action against the use of famous brands in the Metaverse, as well as the legal actions that can be taken by owners of famous brands against the use of their brands in virtual Metaverse products. This study was conducted through a normative juridical approach using literature or secondary data as the main source. Based on the research conducted, it was found that the use of famous brand elements in the Metaverse is considered a violation of the brand, similar to brand violations in the real world in general. Therefore, based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications (Trademark Law) harmonized with the ITE Law, the rights of brand owners to take legal action to protect their brands will still apply even if the brand violations occur in the digital space.